Medicine in Tetyushi in the second half of the nineteenth century - Yelena V. Mironova (Историческая этнология, 2016)
This article discusses the development of healthcare in Tetyushi County in the second half of the nineteenth century. Based on the memories, archival material, and statistical data, in the small town of new hospitals the number of diseases decreased and public health improved, thanks to the efforts of individuals and public institutions. Health workers received relatively low salaries and city-educated doctors missed entertainment and cultural activities. Despite the unfavorable conditions, talented doctors who contributed to extinction of epidemics still worked in Tetyushi. One, V.G. Sirotkin successfully battled typhoid, and A.M. Bogolyubov fought the eternal scourge of the time, trachoma. Connections with various medical organizations that agreed to allocate funds were established. Tetyush County Hospital, located in the city, though it suffered from a lack of beds, not only helped treat the county’s farmers, but also increased their level of confidence in western medicine. The city budget was not large enough to meet all the county’s medical needs, so absorbing costs became mainly the burden of the county district council, which, however, sometimes pressured local doctors in its own interests. During the second half of the nineteenth century, doctors begin to take preventive measures and pay great attention to sanitation, promoting hygiene. The author concludes that health is one of the most important elements in the system of city life and reflects the level of development of Tetyushi.